Estimation of effective dose and organ cancer risk from paediatric computed tomography thorax – abdomen - pelvis examinations - Muhammad, Nor Azura; Abdul Karim, Muhammad Khalis; Abu Hassan, Hasyma; Ahmad Kamarudin, Mazliana; Wong, Jeannie Hsiu Ding; Ibahim, Mohammad Johari (Elsevier, 2019)
Radiation dose exposure in computed tomography (CT) is acknowledged higher when compared to other imaging modalities. The side effects on children have always been a considerable concern. This retrospective study evaluated the dose exposure and organ cancer risk in paediatric patients who underwent CT thorax-abdomen-pelvis (CT TAP) between January 2016 and December 2018. The records of 34 boys and 39 girls (n = 73) were retrieved and divided into three age groups (0–4, 5–9 and 10–12) — the standard protocol for helical scanning setup at 100 kV and 210 mAs. Generally, the CT dose index volume, dose length product and effective dose increased in tandem with the children's age due to higher body mass index. From the youngest to the oldest age group, the liver had the highest cancer risk, especially for boys, which was most likely due to its anatomical location in the scan area. However, from age 5 and above, steep increments were observed in the risk for ovaries, whereas testicles had none. Thus, it is recommended to take precautions when subjecting children to CT TAP, especially prepubescent girls, whose ovaries exposed to almost a thousand times cancer risk per 100,000 procedure.